Impact of a Preset Daily Cell Phone Alarm on Medication Adherence for Aspirin as Antithrombotic Therapy. (September 2019) - Wittig-Wells, Deborah; Higgins, Melinda; Carter, Jessica; Davis, Erica; Holmes, Estella; Jacob, Ani; Samms-McPherson, Jacqueline; Simms, Sandra
Abstract : The ability of patients to adhere to medication regimens is considered critical to achieving optimal results. Many patients are discharged with aspirin (ASA) as an anticoagulant for venous thrombosis embolism prophylaxis after joint replacement surgery. In studies where ASA was prescribed as an antithrombotic after selected orthopaedic surgeries, both lack of understanding and missing doses were identified as factors that affected adherence rates (D. Wittig-Wells et al., 2015, 2017 ). The purpose of this study was to explore the preliminary impact of a preset telephone alarm on medication adherence in adults prescribed ASA for 35 days after knee or hip arthroplasty. This was a randomized controlled trial ( n = 79). Adherence was measured with a four-question self-reporting tool. Average age was 61 years. The majority were female (59.5%) and Caucasian (62.0%) with college or graduate degree-level education (78.5%). When comparing the groups, there were no significant differences between the two groups for the demographics of age, gender, and race. The alarm group had significantly better adherence rates, with fewer people who forgot to take their ASA; only 29.7% of the alarm group ever forgot to take their medication compared with 59.5% of the no-alarm group ( p = .008). It seems that simple cell phone alarms can serve as effective reminders to patients to take selected medications as prescribed.